Nonmarket networks among migrants: Evidence from metropolitan Bangkok, Thailand - Yamauchi, Futoshi; Tanabe, Sakiko (Springer, 2008)
This paper examines the nonmarket interactions among migrants in the urban labor market of Bangkok, Thailand. We test whether the population size and the labor-market performance of previous migrants have externalities to new migrants who have moved from the same province of origin. Our empirical results, which control origin fixed effects, time fixed effects, and origin- and year-specific correlated shocks, show that (1) the relative population size of previous migrants in the market decreases the employment probability of new migrants (substitution effect), (2) the employment probability of previous migrants increases that of new migrants (positive externalities), and (3) when the employment probability of previous migrants is high, however, the scale effect becomes positive, which demonstrates a threshold in the informational scale economies. The results imply that positive informational scale effect dominates negative substitution effect when the efficiency of previous migrants is sufficiently high in the destination labor market